2003
DOI: 10.1002/pmic.200300381
|View full text |Cite
|
Sign up to set email alerts
|

Matrix‐assisted laser desorption/ionization‐ quadrupole ion trap‐time of flight mass spectrometry sequencing resolves structures of unidentified peptides obtained by in‐gel tryptic digestion of haptoglobin derivatives from human plasma proteomes

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 22 publications
0
45
0
1
Order By: Relevance
“…However, several biochemical modifications appear to be superimposed on genetic polymorphisms. Using MS protein structure characterization, the cause of migrational differences of haptoglobin a chains in 2-DE was elucidated [35,36]. It was shown that at least three structurally different protein species can be differentiated and accounted for the most commonly observed spot patterns of haptoglobin a chains.…”
Section: Clinical Applications -Biomarker Identificationmentioning
confidence: 99%
“…However, several biochemical modifications appear to be superimposed on genetic polymorphisms. Using MS protein structure characterization, the cause of migrational differences of haptoglobin a chains in 2-DE was elucidated [35,36]. It was shown that at least three structurally different protein species can be differentiated and accounted for the most commonly observed spot patterns of haptoglobin a chains.…”
Section: Clinical Applications -Biomarker Identificationmentioning
confidence: 99%
“…The resulting IRMPD mass spectra afford more complete sequence coverage for both model peptides and tryptic peptides from cytochrome c. We compare the effectiveness of this derivatization/IRMPD approach to that of a common N-terminal sulfonation reaction that I n recent years, there has been tremendous effort devoted to the application of mass spectrometry to the field of proteomics [1, 2] in large part because of the success of tandem mass spectrometry for elucidation of primary sequences and modifications of peptides and proteins [3][4][5][6][7]. Several ion activation methods have been developed in this context, including collision induced dissociation (CID) [8,9], electron capture dissociation (ECD) [10]. electron-transfer dissociation (ETD) [11], pulsed-Q dissociation (PQD) [12], surface induced dissociation [13], and photodissociation (PD) [14 -19].…”
mentioning
confidence: 99%
“…Several ion activation methods have been developed in this context, including collision induced dissociation (CID) [8,9], electron capture dissociation (ECD) [10]. electron-transfer dissociation (ETD) [11], pulsed-Q dissociation (PQD) [12], surface induced dissociation [13], and photodissociation (PD) [14 -19].…”
mentioning
confidence: 99%
“…Concatenating the differences between successive entries in compositional series yields peptide sequences that can be scored and ranked according to signal intensity. , examples persist of demand for fast and reliable peptide sequencing due to incomplete or inadequate databases [5][6][7][8][9]. De novo peptide sequencing algorithms also abound [5, 10 -17], but objective assessments of de novo peptide sequencing capabilities with unknowns [18] indicate that much work remains.…”
mentioning
confidence: 99%